Super 8 [videorecording (DVD)] - Abrams, J. J. (Jeffrey Jacob), 1966-; Spielberg, Steven, 1946-; Fanning, Elle, 1998-; Michalka, A. J. (Amanda Joy), 1991-; Chandler, Kyle; Courtney, Joel, 1996-; Lee, Ryan, 1996- (Paramount Home Entertainment, 2011)
In the summer of 1979, a group of friends in a small Ohio town witnesses a catastrophic train crash while making a super 8 movie and soon they suspect that it was not an accident. Shortly after, unusual disappearances and inexplicable events begin to take place in town, and the local deputy tries to uncover the truth, something more terrifying than any of them could have imagined.